2019
DOI: 10.1038/s41467-019-09627-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular architecture on ring polymer dynamics in semidilute linear polymer solutions

Abstract: Understanding the dynamics of ring polymers is a particularly challenging yet interesting problem in soft materials. Despite recent progress, a complete understanding of the nonequilibrium behavior of ring polymers has not yet been achieved. In this work, we directly observe the flow dynamics of DNA-based rings in semidilute linear polymer solutions using single molecule techniques. Our results reveal strikingly large conformational fluctuations of rings in extensional flow long after the initial transient str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 49 publications
2
79
2
Order By: Relevance
“…Indeed, ring DNA tracers embedded in solutions of entangled linear DNA have been reported to have diffusion coefficients up to an order of magnitude lower than their linear DNA equivalents (34,46,50), a phenomenon which has been attributed to threading events. Simulations have also shown that threading leads to anomalous diffusion and swelling of DNA coils (47)(48)(49)54) similar to our results. Finally, large fluctuations in the relaxation dynamics of ring DNA embedded in semidilute linear DNA solutions have recently been observed and attributed to threading events (49).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, ring DNA tracers embedded in solutions of entangled linear DNA have been reported to have diffusion coefficients up to an order of magnitude lower than their linear DNA equivalents (34,46,50), a phenomenon which has been attributed to threading events. Simulations have also shown that threading leads to anomalous diffusion and swelling of DNA coils (47)(48)(49)54) similar to our results. Finally, large fluctuations in the relaxation dynamics of ring DNA embedded in semidilute linear DNA solutions have recently been observed and attributed to threading events (49).…”
Section: Discussionsupporting
confidence: 90%
“…Simulations have shown that these multiple diffusive modes, and the interconversion between them, leads to heterogeneous transport and conformations of rings (54)(55)(56). However, experimental evidence for these varied transport modes and conformations is sparse (49,50,57). Further, how these idealized models translate to complex biological systems, such as DNA diffusion through the cytoskeleton, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The ring topology is also important for stabilizing links. Unlike the recently observed transient hooking of rings by linear chains [11], ring-ring links cannot be destroyed by convective-constraint release because rings lack ends. Figure 5(a) plots the fraction of topologically linked rings φ top at the terminal strain for all W i of the N = 400 melt.…”
contrasting
confidence: 57%
“…Microscopic measures of ring entropy directly relate the nonlinear rise in stress to elongated supramolecular clusters. Unlike the transient "hooking" of rings by linear chains [11], these new ring-ring links are pulled tight and stabilized by the flow. Thus, supramolecules can persist even if W i is changed.…”
mentioning
confidence: 95%
“…Most experimental studies on entangled polymers to date have focused on linear chains, although there is growing interest in more complex topologies, such as circular chains [24][25][26]. Recently, our group performed single-molecule experiments to compress and induce self-entanglements in circular DNA with electric fields, with self-entanglements serving as a minimal system for studying chain entanglements [27].…”
Section: Introductionmentioning
confidence: 99%